PEMBERIAN JASA HUKUM DALAM PERKARA PIDANA OLEH ADVOKAT YANG BELUM TERDAFTAR BERDASARKAN UNDANG-UNDANG NOMOR 18 TAHUN 2003 TENTANG ADVOKAT DAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 6 TAHUN 2004 - Buana, Kelbi Fadila; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Registered and unregistered advocates are one of the law enforcers who are assigned to provide legal aid or legal services to people facing legal issues. In article 1, paragraph 1 of the Law of 2003 on advocacy explains that in carrying out its duties advocates include good work done in court (litigation) or out of court (non ligitasi). For unregistered advocates can provide legal services with non-litigation task that is outside the court such as providing consultation, mediation and so forth. The purpose of this study is to determine the regulation of legal services in criminal cases by advocates who have not registered under Law No. 18 of 2003 on Advocates and Decisions of the Constitutional Court Number 6 Year 2004 and to determine the form of responsibility of providing legal services in criminal cases by advocates who Has not been registered pursuant to Law Number 18 Year 2003 regarding Advocate and Constitutional Court Decision Number 6 Year 2004.This type of research is normative legal research that focuses on the level of legal syncrosion with document studies about the provision of legal services in criminal cases by advocates who have not registered under Law No. 18 of 2003 on Advocates and Decisions of the Constitutional Court Number 6 Year 2004 while when viewed fromtThe nature of this research is descriptive. This research uses secondary data that has been so.The result of this study is the regulation of providing legal services in criminal cases by advocates who have not registered under Law No. 18 of 2003 on Advocates and Constitutional Court Decision Number 6 of 2004 that the provision of legal services is not limited only by advocates, especially legal services outside the court. In the verdict, it does not merely express non binding provisions of Article 31 but also at the same time removes restrictions that only advocates are allowed to practice legal services. Outside advocates are not prohibited to provide legal services as long as the interests require and not contrary to the laws and regulations. The form of accountability for the provision of legal services in a criminal case by an advocate who has not been registered pursuant to Law Number 18 Year 2003 regarding Advocate is in the form of oral reprimands, written warning, temporary discharge from his profession for 3 (three) to 12 (twelve) months and permanent dismissal of his profession. Based on the decision of the Constitutional Court Number 6 Year 2004 adjusted to Law Number 18 Year 2003 regarding Advocate.Keywords: Legal services, unregistered advocates.